Analysis of Back Groups Take-Off In South Kalimantan Diving Athletes - Fadillah, Muhammad Ryan; Indah, Eka Purnama; Kahri, Ma’ruful (UNIVERSITAS NEGERI MAKASSAR, 2025)
Diving is a sport that resembles aerial acrobatics above the surface of the water. Diving is usually done from a springboard Diving consists of a jump that starts from a take-off or bounce step, then enters the water. This research aims to find out about beautiful jumping movements when taking off National Games (PON) for South Kalimantan athletes. This study uses descriptive evaluative research methods. The population in this study was South Kalimantan diving athletes who took part in PON activities totalling 5 people the sample used in this research used the Purposive Sampling method and based on men’s platform were 2 people participating in PON activities. The results of the research show that the beautiful diving skills in taking off in the diving athletes participating in the South Kalimantan National Sports Week fall into the